Search and modification of ARQ protocols for point-to-point communication channels with high error rate - Castillano, Gregor C. (1997)
In data communication systems over a channel in which error rate is very high, reliability of the data transmission is one of the main concerns. Error detection incorporated with automatic-repeat-request (ARQ) techniques are widely used for error control. This method is simple and provides high system reliability. The first part of this study compiles the different version of automatic-repeat-request (ARQ) protocols gathered from different international journals, published international papers and books. In this part, the performance of different ARQ protocols for point-to-point data transmission over half-duplex and full-duplex channels are analyzed and compared. The results of comparison are used to determine which of the different versions of ARQ protocols being analyzed are workable over high error rate communication channels. Throughput determination and analysis are also discussed in this study. The second part of this study presents some techniques that modify Go-back-N and Stop-and-Wait ARQ protocols with the aim of increasing the throughput efficiency under high error rate conditions with less additional complexity in system implementation. The proposed modifications of the two ARQ protocols are perfrormed by theoretical analysis. The results of ARQ protocols modification show improvement of the throughput efficiency of communication channels under high error rate conditions. The three main ARQ protocols used in this study are the stop-and-wait (SW), go-back-N (GBN), and selective-repeat (SR) ARQ protocols.
Computer print-out.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Automatic-repeat-request protocols; Data transmission system; Data transmission system; Error correcting codes (Information theory)